Women-led community-based rice seed entrepreneurship model in Bangladesh: Status, challenges and opportunities - Nuruzzaman,; Islam, Afrad Md Safiul; Haque, Md. Enamul; Nahar, Ashrafun; Habib, Muhammad Ashraful; Nayak, Swati; Islam, Saidul; Rashid, Md. Mamunur; Biswas, Amlan (Informa UK Limited, 2023)
The study assessed the overall status of CBRSEM and the potential benefits accrued from the model. The sample comprised 92 respondents selected from a women-led Community-Based Rice Seed Entrepreneurship Model (CBRSEM) located in Taraganj and Shadullapur upazilas of the Rangpur and Gaibandha districts of Bangladesh, respectively, following a stratified proportionate random sampling technique. Membership in CBRSEM developed their communication skills, social relationships, and decision-making abilities while capacitating them in sowing, harvesting, and threshing. Increased access to quality seeds was ensured through easy availability at the right time in proximity. Increased yield, betterment of livelihood, and empowerment were the leading benefits. The concerns that emerged were high production cost, absence of a moisture meter, and timely roguing. Popular suggestions put forward included means to lessen the cost of agricultural inputs, provision of loans with easy terms and conditions, and training programs